AT-TA’DIB: ISLAMIC SOLUTION FOR NEGLECTFUL PARENTING - Abror, Ahmad Auladul; Nisa, Ulfatun Wahidatun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Parents in the family have roles and responsibilities towards their children. Every parent wants to have a child who has a good moral personality or is pious. To achieve this desire, parents are expected to optimize their roles and responsibilities as parents towards their children. Parenting and educating children is carried out by various kinds of parenting patterns such as democratic; authoritarian; permissive; and neglect (indifferent). The parenting style in this discussion is neglectful parenting. This parenting style is a parenting style that pays little attention to the child and parents are more concerned with the parents own personality. In this writing, we use the library study method to provide solutions for good Islamic education patterns. Which is where parenting patterns in Islam are in accordance with Islamic teachings which will improve parenting patterns for children in the midst of modern era developments.